Immune Activation among Maltreated and Non-maltreated Children. (September 2021) - Kertes, D.A.; Leri, J.; Clendinen, C.; Thompson, L.; Rosenthal, C.; Bright, M.
Abstract : Background: Child maltreatment has widespread biological and social impacts with consequences for social and academic functioning as well as physical and emotional health outcomes. Little is known about maltreatment impacts on immune function in young children. This study examined immune activation following routine inoculation among maltreated and non-maltreated children. Methods: Children aged 12-60 mos were recruited from general pediatric and child protection team clinics (N=35; 43% female). Physical abuse/neglect was verified from child protective service records. Blood samples were collected prior to influenza immunization, and 4- and 8- week follow-up. Influenza IgG and IgM levels were quantified by enzyme-linked immunosorbent assay and analyzed for change over time, controlling for age and sex. Results: Maltreated and non-maltreated children showed different patterns of immune activation following routine immunization. Case report data supported the efficacy of booster doses. Conclusion: These findings suggest maltreatment has direct impacts on immune system reactivity to immunization, with potential impacts for health.